Myeloid-Derived Suppressor Cells Are Increased in Lung Transplant Recipients and Regulated by Immunosuppressive Therapy - Iglesias-Escudero, María; Segundo, David San; Merino-Fernandez, David; Mora-Cuesta, Victor M.; Lamadrid, Patricia; Alonso-Peña, Marta; Raso, Sandra; Iturbe, David; Fernandez-Rozas, Sonia; Cifrian, Jose; López-Hoyos, Marcos (Frontiers in Immunology, 2022)
Lung transplantation is a primary therapy in patients with end-stage lung diseases. Although remarkable improvement has been achieved due to the immunosuppressive protocols, 5-year survival for lung transplant recipients (LTR) remains low. An increasing field of research is focused on the study of dysregulation of immune mechanisms underlying allograft failure. In this regard, myeloid-derived suppressor cells (MDSCs) represent a heterogeneous group of myeloid regulatory cells that were originally described in cancer. Several studies in animal models point to them as important players in the induction of allograft tolerance, due to their immune modulatory function, but there is a lack of studies regarding their role in human transplantation. Here, we describe for the first time circulating subsets MDSCs from LTR at several time points and we evaluated the relationship of MDSCs with sort-term lung transplant outcomes. Although no effect of MDSCs subsets on short-term clinical events was observed, our results determine that Mo-MDSCs frequencies are increased after acute cellular rejection (ACR), suggesting a possible role for Mo-MDSC in the development of chronic lung allograft dysfunction (CLAD). Therefore, whether MDSCs subsets play a role as biomarkers of chronic rejection remains unknown and requires further investigations. Finally, the effects of different immunosuppressive drugs on the development and function of MDSCs need to be better characterized and further prospective studies are required to establish whether long-term tolerance to immune modulation transplantation is dependent on MDSCs.